Increased Cell Proliferation and Gene Expression of Genes Related to Bone Remodeling, Cell Adhesion and Collagen Metabolism in the Periodontal Ligament of Unopposed Molars in Growing Rats - Dorotheou, Domna; Farsadaki, Vassiliki; Bochaton-Piallat, Marie-Luce; Giannopoulou, Catherine; Halazonetis, Thanos D.; Kiliaridis, Stavros (Frontiers in Physiology, 2017)
Tooth eruption, the process by which teeth emerge from within the alveolar bone into the oral cavity, is poorly understood. The post-emergent phase of tooth eruption continues throughout life, in particular, if teeth are not opposed by antagonists. The aim of the present study was to better understand the molecular processes underlying post-emergent tooth eruption. Towards this goal, we removed the crowns of the maxillary molars on one side of the mouth of fourteen young rats and examined gene expression patterns in the periodontal ligaments (PDLs) of the ipsilateral and contralateral mandibular molars, three and fifteen days later. Nine untreated rats served as controls. Expression of six genes, Adamts18, Ostn, P4ha3, Panx3, Pth1r and Tnmd, was upregulated in unopposed molars relative to molars with antagonists. These genes function in osteoblast differentiation and proliferation, cell adhesion and collagen metabolism. Proliferation of PDL cells also increased following loss of the antagonist teeth. Interestingly, mutations in PTH1R have been linked to defects in the post-emergent phase of tooth eruption in humans. We conclude that post-emergent eruption of unopposed teeth is associated with gene expression patterns conducive to alveolar bone formation and PDL remodelling.